C++ Primer For Non C Programmers - Zamir, Saba (New York Mcgraw-Hill Book Company, Inc., 1995)
An introduction to the power and application potential of C++, assuming no C programming background. A book that not only teaches C++, but also demonstrates clearly why the move to modular, non-procedural programming and object-oriented design is dominant and preferable.
ENG